Changes in Behavior and Ultrasonic Vocalizations During Pair Bonding and in Response to an Infidelity Challenge in Monogamous California Mice - Pultorak, Joshua D.; Alger, Sarah J.; Loria, Steven O.; Johnson, Aaron M.; Marler, Catherine A. (Frontiers in Ecology and Evolution, 2018)
Despite recent exciting research about pair bonding, little is known about how mammalian vocalizations change with the initiation and maintenance of pair bonding in monogamous species. Moreover, even less is known about the significance of pair bond resilience in the face of social challenges. In the strictly monogamous California mouse (Peromyscus californicus), we measured changes in ultrasonic vocalizations (USV) and other behaviors within male-female dyads over the course of pair bonding and characterized associations of USVs with affiliation and aggression. After one week of cohabitation, pairs exhibited decreased aggression and “bark” USVs, and increased “simple sweep” and “sustained vocalization” (SV) USV types. Accordingly, the number of barks was associated with aggression, whereas the number of simple sweeps and the number, call duration and bout size of SVs corresponded with affiliation. We then experimentally assessed the impact of an infidelity challenge (one week cohabitation with an unfamiliar, opposite-sex, extra-pair individual) for both sexes on pair social behavior, acoustic behavior, and reproductive success. The infidelity challenge temporarily disrupted pair bond interactions during pair reunion, independent of which sex experienced the infidelity challenge, via both increases in aggression and barks, and a stunting of affiliation and SVs, compared to control pairs. Pair reproductive success, in the form of birth latency, litter size, pup survival and birth weight, did not differ between infidelity challenge pairs and controls. The quality of pair interactions, however, was associated with reproductive success: aggression during pair reunion across all pairs was associated with a lower likelihood of successfully producing a litter. Similarly, among infidelity challenge pairs, but not the controls, there was a positive association between pair affiliation and paternal care, and a negative association between pair aggression and paternal care. Overall, the infidelity challenge revealed a weak negative effect on reproductive success, but we speculate, based on our results, that greater resiliency of a pair bond can moderate negative effects of a social challenge.